NEED ANALYSIS: DEVELOPMENT OF LK-D&T SKETCH MODULE FOR FORM ONE DESIGN AND TECHNOLOGY (D&T) SUBJECT IN SECONDARY SCHOOL - Nor Anisah Ahmad; Ridzwan Che Ros; Arasinah Kamis; Hawa Naqiah Makmor (Universitas Ahmad Dahlan, 2019)
This study is a need analysis of the development of sketch module for secondary D&T students. This study is in a form of a survey using questionnaire as a research instrument. A total of 287 teachers were involved in the study sample. The study sample was randomly selected. The data were analyzed using a descriptive analysis to meet the objectives of the study. The findings show that teachers are facing difficulties in implementing D&T teaching in schools. The majority of teaching teachers consist of non-option D&T teachers, lack of D&T knowledge and skills, intensive course requirements, less teaching aids and less conducive workshops. Students found that it was difficult to master topics that the teachers teach, especially the topic of sketching. The majority of teachers agree that the topic of sketching ought to be developed in a way to enhance students understanding, and along with helping the less skilled teachers. The implication of the study is that this module can be used by D&T teachers and students as a reference to improve the teaching and learning to become more effective.